2021
DOI: 10.1007/s00345-021-03876-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum levels of microRNA-371a-3p (M371) with risk factors for progression in nonseminomatous testicular germ cell tumours clinical stage 1

Abstract: Purpose Lymphovascular invasion (LV1) and presence of > 50% embryonal carcinoma (> 50% EC) represent risk factors for progression in patients with clinical stage 1 (CS1) nonseminomatous (NS) testicular germ cell tumours. As serum levels of microRNA-371a-3p (M371) are capable of detecting small amounts of GCT, we evaluated if LV1 and > 50% EC are associated with M371 levels. Methods M371 serum levels were measured postoperatively in 153 NS CS1 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In Dieckmann's large prospective study, relatively few tumours <10 mm were included. 29 Nevertheless, while the sensitivity of miR-371a-3p remained high for those patients with NSGCTs <10 mm, it dropped to 60% for seminomas <10 mm. Radtke et al examined 27 patients with GCNIS only and found that only half (51.9%) had miR-371a-3p elevations in a seemingly 'dose-dependent' manner with highest levels among those with bilateral GCNIS.…”
Section: Diagnosis-before and After Orchiectomymentioning
confidence: 92%
See 2 more Smart Citations
“…In Dieckmann's large prospective study, relatively few tumours <10 mm were included. 29 Nevertheless, while the sensitivity of miR-371a-3p remained high for those patients with NSGCTs <10 mm, it dropped to 60% for seminomas <10 mm. Radtke et al examined 27 patients with GCNIS only and found that only half (51.9%) had miR-371a-3p elevations in a seemingly 'dose-dependent' manner with highest levels among those with bilateral GCNIS.…”
Section: Diagnosis-before and After Orchiectomymentioning
confidence: 92%
“…In a similar study, Dieckmann et al . showed that in 18 CS II and in nine CS III patients, miR‐371a‐3p levels dropped to zero after chemotherapy, in all but two (7%) patients 29 …”
Section: Cs‐ii/iii Monitoring Treatment Responsementioning
confidence: 98%
See 1 more Smart Citation
“…In 2022 Dieckmann et al. found a significant association between preoperative miR‐371a‐3p levels and classical histopathological risk factors of relapse (vascular invasion and >50% embryonal carcinoma) in serum of 131 patients 107 . Also, Fankhauser et al.…”
Section: Testicular Cancermentioning
confidence: 97%
“…In this special issue, many of the above-mentioned prerequisites to treat patients suffering from germ cell tumors with cutting-edge knowledge and technology are presented by international experts in the field. The modern diagnostic work-up as presented by Zengerling [ 1 ], Belge [ 2 ], and Brandt [ 3 ] et al will soon include not only magnetic resonance imaging to avoid diagnostic toxicity in young ages, but will also include new tumor markers, like microRNA371a-3p, for better non-invasive staging. The consequence of this more precise staging possibilities may be the broader indication for local and less traumatic treatment options like robotic RPLND and resection of small seminoma metastases as presented by Hamilton [ 4 ] and Daneshmand et al[ 5 ].…”
mentioning
confidence: 99%